Avoiding bites and scratches? Understanding the public health implication of human–bat interactions in Ghana. (14th November 2018) - Lawson, Elaine T.; Ayivor, Jesse S.; Ohemeng, Fidelia; Ntiamoa‐Baidu, Yaa
Abstract: Zoonotic pathogens cause an estimated 70% of emerging and re‐emerging infectious diseases in humans, affecting various aspects of human development on a global scale. The significance of bats as a source of emerging infectious diseases is being progressively appreciated. This study was undertaken post‐Ebola virus disease in West Africa and assessed the public health implications of human–bat interactions by exploring the reasons for contact between humans and bats, as well as reported actions taken upon experiencing bat bites or scratches. The paper highlights the nuances of human–bat interactions, stressing zoonotic disease risk awareness as well as the sources of information. The study used questionnaires to solicit information from 788 respondents in five communities with significant bat populations. We show that bat consumption was one of the main reasons for human–bat interactions. More men across the various communities ate bat meat. Only a small number of respondents (4.4%) reported being bitten by a bat, and 6.1% had been scratched by a bat. More than 21% had come into direct contact with bat blood. An even lower number went to the hospital after been bitten or scratched by bats. There was little knowledge on post‐exposure management. The most common places human–bat interactions occurred were at home and on farms. Seventy‐three per cent of the respondents believed that bats carried diseases, with Ebola virus disease being the most mentioned. Respondents indicated that the way they interacted with bats had not changed, even though they believed bats carried diseases and 46% stated that they had not changed the way they interacted with bats over the last two years. Apart from providing information on avoiding bites and scratches, a more holistic framework is needed to reduce human–bat interactions. The paper recommends a comprehensive and coordinated approach to optimizing an effective response to a potential bat‐borne zoonotic disease spillover.